Effect of rewetting solutions on micropush-out dentin bond strength of new bioceramic endodontic material - Giovana Cunha GRITTI; Salma Ivanna Araújo CAVALCANTE; Etevaldo Matos MAIA-FILHO; José BAUER; Matheus Coêlho BANDÉCA; Giulio GAVINI; Ceci Nunes CARVALHO (Sociedade Brasileira de Pesquisa Odontológica, 2017)
Abstract To evaluate the influence of rewetting solutions on bond strength to root dentin of conventional gutta-percha (GP) or niobium phosphate glass-based gutta-percha (GNb) associated with a bioceramic sealer. The root canals of 80 human mandibular premolars were prepared using nickel-titanium instruments and irrigation with sodium hypochlorite and EDTA. The teeth were randomly divided into four groups according to the gutta-percha used: GNb or GP associated with EndoSequence BC Sealer (BC) and the solution for rewetting dentin before filling (distilled water; phosphate buffer saline solution - PBS; simulated body fluid - SBF; or no solution). The root canals were filled with a single cone using warm vertical condensation. Micropush-out bond strengths associated with the filling materials in slices from middle root thirds was determined 30 days after root filling. The failure mode was analyzed with stereoscopic lens. The data were statistically analyzed by two-way ANOVA and Holm-Sidak test (p < 0.05). There was significant difference in the types of gutta-percha (p < 0.001) and in the different rewetting solutions (p = 0.003). The interaction between gutta-percha and rewetting solutions was not significant (p = 0.53). The SBF solution provided an increase in bond strength for both gutta-percha solutions. The GNb+BC (3.42 MPa) association increased bond strength when compared with GP+BC (2.0 MPa). The use of SBF as a dentin rewetting solution increased bond strength in the groups studied. Association of GNb with bioceramic sealer was beneficial, increasing the bond strength to dentin when compared with the association with GP.